Brief communication: virological outcomes and dolutegravir resistance mutations in HIV-infected patients: a multicenter retrospective cohort study in Mozambique - Anna Maria Doro Altan; Noorjehan Majid; Stefano Orlando; Elton Uamusse; Marcia Rafael; Zita Sidumo; Giovanni Guidotti; Fausto Ciccacci (AIDS Research and Therapy)
Abstract The global HIV epidemic remains a major public health challenge, with DTG playing a key role in ART regimens due to its efficacy and tolerability. This study evaluated virological outcomes and resistance mutations in patients on DTG in Mozambique through a retrospective cohort study in seven DREAM centers. Data from 29,601 patients (98.1% on DTG) revealed a virological suppression rate of 95% (27,622/29,051). Factors positively associated with suppression included age > 50, longer ART duration, and being female. Of 17 resistance tests, 8 showed major mutations, including G118R and E138K. Results highlight DTG’s effectiveness and the need for resistance surveillance.